Analysis Of Batak Culture-Based Multicultural Christian Religious Education Concepts And Their Implementation In Christian Religious Education At The Quality Berastagi University (UQB) - Yosefo Gule; Angel Aulia Bukit (Journal on Education, 2023)
This article aims to describe the concept of multicultural Christian Religious Education based on Batak culture and its implementation in Christian Religious Education learning at the Quality Berastagi University (UQB), taking into account that the Quality Berastagi University (UQB) student population is comprised of students of diverse ethnicities, languages, and religions. different. Its variety is a national advantage and source of riches that must be preserved. This article employs a descriptive qualitative study approach and a library research design for its research methodology. The findings of the researchers indicate that the concept of multicultural Christian Religious Education based on Batak culture can be implemented in a number of ways: First, through the teaching and learning process in the classroom, specifically through the presentation of material that integrates it through educational themes. Relevant Christianity; Second, through daily campus activities, such as co-curricular and extracurricular activities, connected to establishing the values of the "Dalihan na Tolu" philosophy, which emphasizes: first, Greetings as the Base of Familiarity. Second, an attitude of consensus and respect for others' opinions. Third, the tolerance for life attitude. Fourth, brotherhood and mutual assistance. These findings add to the efforts of educators in delivering multicultural Batak-based Christian Religious Education content through the "Dalihan na Tolu" philosophy in the Christian Religious Education learning process at the Quality Berastagi University (UQB).